Materials Processing Fundamentals 2017 - Allanore, Antoine; Lambotte, Guillaume; Lee, Jonghyun (The Minerals, Metals & Materials Series, 2017)
Covering the physical and numerical modeling of materials processing, this book includes contributions across the range of metals and minerals. This collection offers a unique opportunity to present models and results for key processes involved in extraction, joining, separation, and casting of materials. The corresponding fundamentals of mass and heat transport as well as physical and thermodynamics properties are addressed, allowing for a cross-disciplinary vision of the field.